Analysis And Implementation Of Wireless Sensor Network Parameters Using Neural Networks (Journal of Namibian Studies : History Politics Culture, 2023)
In an era where the proliferation of wireless sensor networks (WSNs) is integral to the technological underpinnings of various sectors including environmental monitoring, healthcare, and smart infrastructure, optimizing the operational parameters of these networks has emerged as a critical challenge. The dynamic and heterogeneous nature of WSN environments necessitates adaptive and intelligent solutions for parameter optimization to ensure optimal performance, longevity, and energy efficiency. This research, encapsulated in the paper titled "Analysis and Implementation of Wireless Sensor Network Parameters Using Neural Networks," introduces an innovative approach employing neural network techniques to systematically analyze and enhance WSN parameters.This study embarks on a detailed investigation into the application of neural networksas a potent tool for the optimization of key WSN parameters. The methodology is grounded in the development and deployment of a tailored neural network model designed to adaptively learn and optimize from WSN operational data. The model focuses on critical parameters such as energy consumption, network lifetime, and data accuracy, which are pivotal for the efficiency and sustainability of sensor networks. Through rigorous training and validation processes, the neural network model is fine-tuned to predict and optimize network performance under varying conditions.The findings of this research are both significant and illuminating, showcasing the neural network model's capability to markedly improve WSN parameters. Comparative analyses highlight the model's superior performance in optimizing network efficiency and resource utilization when juxtaposed with conventional optimization methodologies. This underscores the potential of neural networks in revolutionizing WSN management and deployment strategies.The implications of this study are far-reaching, offering a novel perspective on harnessing the power of machine learning for WSN optimization. It opens new avenues for research and development in the field, suggesting that neural network- based approaches can significantly contribute to the advancement of intelligent and autonomous WSNs. This research not only enriches the academic discourse on wireless sensor networks but also lays a foundational framework for future innovations aimed at enhancing the operational efficacy of these critical networks.In essence, "Analysis and Implementation of Wireless Sensor Network Parameters Using Neural Networks" delineates a groundbreaking approach to overcoming the challenges of WSN parameter optimization. The integration of neural networks paves the way for the development of smarter, more efficient, and more adaptable wireless sensor networks, heralding a new era in the application and management of these systems. The study's contributions are poised to have a lasting impact on the field, driving further exploration and innovation in the optimization of wireless sensor networks through advanced machine learning techniques.